Finding the path(s) towards profitable e-commerce - Jacques Bughin (Deutsche Bank Research, 2003)
Relying on a unique and arguably representative sample of transaction e-commerce companies, this paper takes a closer look at whether and how companies could be profitable on-line. This analysis clearly demonstrates that a non-trivial set of winners are emerging, which combine both strong operational excellence as well as fine-tuned to about 3 generic strategic postures.
Keywords: 330; E-tailing; Strategic Clusters; Post entry performance; E-Business; Online-Handel; Rentabilität; Schätzung; Welt